Deliberate reserve creation: an interim solution - OSSOLA, R. (PSL Quarterly Review, 2014)
<!–[if gte mso 9]> 72 1024x768 <![endif]–> The author considers recent developments in international monetary system reform. He highlights this disagreements, especially on the side of France, with in the Group of Ten. He therefore foresees a general scarcity of reserve assets and proposes a plan for reserve creation to be activated under conditions of a better balance of payments equilibrium between members and a better working of the adjustment process. JEL: E42, F32, F33 <!–[if gte mso 9]> Normal 0 14 <![endif]–><!–[if !mso]> <![endif]–><!–[if gte mso 10]> <![endif]–>